Caring during clinical practice: Midwives' perspective - Mmajapi E. Chokwe; Susan C.D. Wright (AOSIS, 2013)
Background: Caring forms the core of nursing and midwifery. Despite caring being an important emotional aspect of midwifery and nursing, there are general public complaints about uncaring behaviour in midwifery. Therefore, there is a need to explore caring from midwives' point of view with the hope of identifying solutions and recommendations for midwifery practice. Furthermore, the study aimed to stimulate debate and discussion about the caring behaviour of midwives.Objective: To explore caring during clinical practice as perceived and experienced by midwives.Method: The study was contextual, exploratory and qualitative. The participants were midwives working in state and private hospitals in Tshwane,South Africa where BTech II and III midwifery learners were allocated for work integrated learning (WIL). Data collection was carried out through self-report using a questionnaire and focus group. Questionnaires were distributed to 40 midwives at private and state hospitals in Tshwane. This was followed by two focus group sessions to ensure that data is enriched. The hermeneutic interpretive approach was used to analyse data, and analysis continued until saturation.Results: Themes of caring and uncaring related to patient care and midwives emerged. Thefindings illustrated that the midwives had excellent theoretical knowledge of caring, but someof them did not display caring behaviour during clinical practice.Conclusion: Some of the midwives did not display caring behaviour. Implication for practicewas provided based on the research findings. Recommendations included measures of improving caring behaviours during midwifery practice.